Financial Reporting Quality of the Manufacturing Firms Listed in Indonesian Stock Exchange - Muhammad Reza; Syed Ehsan Ullah (LifeSciFi, 2019)
The purpose of the study is to empirically investigate the financial reporting quality of listed manufacturing firms in Indonesian Stock Exchange. The study has collected 287 responses from the financial officers and experts of 89 IDX-listed manufacturing firms using a five-point Likert scale instrument based on the nonprobability purposive sampling technique. The study has employed PLS-SEM using SmartPLS version 3.2.8 for data analysis. The results have shown that hypothesis-1 postulating that CSR has significantly positive effect on financial reporting quality has been accepted while hypothesis-2 suggesting that environmental performance has a significant and positive effect on financial reporting quality. The managers are recommended to see whether their accountants are from a single interface by ensuring that both funds are linked together, and reconciliations meet the balances of the trial balance.